Physiological resilience of pink salmon to naturally occurring ocean acidification - Frommel, Andrea Y (Conserv Physiol, 2020)
Pacific salmon stocks are in decline with climate change named as a contributing factor. The North Pacific coast of British Columbia is characterized by strong temporal and spatial heterogeneity in ocean conditions with upwelling events elevating CO(2) levels up to 10-fold those of pre-industrial global averages. Early life stages of pink salmon have been shown to be affected by these CO(2) levels, and juveniles naturally migrate through regions of high CO(2) during the energetically costly phase of smoltification. To investigate the physiological response of out-migrating wild juvenile pink salmon to these naturally occurring elevated CO(2) levels, we captured fish in Georgia Strait, British Columbia and transported them to a marine lab (Hakai Institute, Quadra Island) where fish were exposed to one of three CO(2) levels (850, 1500 and 2000 μatm CO(2)) for 2 weeks. At ½, 1 and 2 weeks of exposure, we measured their weight and length to calculate condition factor (Fulton’s K), as well as haematocrit and plasma [Cl(−)]. At each of these times, two additional stressors were imposed (hypoxia and temperature) to provide further insight into their physiological condition. Juvenile pink salmon were largely robust to elevated CO(2) concentrations up to 2000 μatm CO(2), with no mortality or change in condition factor over the 2-week exposure duration. After 1 week of exposure, temperature and hypoxia tolerance were significantly reduced in high CO(2), an effect that did not persist to 2 weeks of exposure. Haematocrit was increased by 20% after 2 weeks in the CO(2) treatments relative to the initial measurements, while plasma [Cl(−)] was not significantly different. Taken together, these data indicate that juvenile pink salmon are quite resilient to naturally occurring high CO(2) levels during their ocean outmigration.